Rekonstruksi Model Persiapan TOAFL Berbasis Pembelajaran Kooperatif: Studi Multi Kasus di UIN Tulungagung dan UIN Malang - Ahmad Nurcholis; Timbul Timbul; Muhamad Asngad Rudisunhaji (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2026)
This study explores the reinvention of TOAFL preparation through the implementation of Cooperative Learning as an innovative pedagogical framework in Islamic higher education. Conducted as a multiple case study at UIN Sayyid Ali Rahmatullah Tulungagung and UIN Maulana Malik Ibrahim Malang, this research investigates how cooperative learning models reshape instructional practices, student engagement, and academic Arabic proficiency in high-stakes standardized testing contexts. Grounded in Social Interdependence Theory, the study examines how positive interdependence, individual accountability, promotive interaction, and collaborative skills are operationalized in TOAFL classrooms. Data were collected through in-depth interviews, classroom observations, and document analysis, involving lecturers, program coordinators, and students participating in TOAFL preparation programs. The findings reveal that cooperative learning not only enhances students’ linguistic competence including listening, structure, and reading skills but also fosters higher-order thinking, peer scaffolding, and adaptive learning strategies aligned with the demands of 21st-century education. Furthermore, the study demonstrates that collaborative learning environments contribute to increased motivation, reduced test anxiety, and stronger academic resilience. Institutional culture and lecturer innovation emerge as critical factors in sustaining the transformation of TOAFL pedagogy. This research proposes a future-oriented model of TOAFL preparation that integrates collaborative learning principles with digital support systems, positioning cooperative learning as a strategic framework for strengthening academic Arabic proficiency in Islamic universities. The study contributes theoretically to the application of Social Interdependence Theory in standardized language assessment contexts and practically to the development of adaptive, student-centered TOAFL programs in contemporary higher education.